Prevalensi skabies pada santri laki-laki Pondok Pesantren Darul Istiqamah Manado tahun 2023 - Fikri, Muhammad; Wahongan, Greta Jane Pauline; Bernadus, Janno Berty Bradly; Tuda, Josef Sem Berth (UNIVERSITAS SAM RATULANGI, 2024)
Background: Scabies is a dermatological issue caused by the parasitic mite Sarcoptes scabiei var. hominis. The occurrence of scabies tends to easily spread, both directly through skin-to-skin contact and indirectly through shared objects. Scabies infections commonly occur in individuals residing in communal settings, such as dormitories and boarding schools. Aim: The aim of this research is to depict the magnitude and prevalence rate among male students at Pondok Pesantren Darul Istiqamah. Methods: Conducted as a descriptive survey employing the cross-sectional method, this research quantifies the prevalence of scabies among male students at Pondok Pesantren Darul Istiqamah during the period from October to November 2023. The diagnostic process is based on four cardinal signs, with confirmation through laboratory tests. Results: All male students (75 students) were selected as research subjects based on inclusion criteria. The research findings indicate that 56% or 42 out of 75 sampled students had scabies infections. Conclusion: The conclusion drawn from this study is that the prevalence of scabies among students at Pondok Pesantren Darul Istiqamah is notably high. Keywords: prevalence of scabies, scabies, Sarcoptes scabiei, Islamic boarding school